Capacitor voltage balancing method for modified modular multilevel converter. Issue 8 (10th April 2018) - Luo, Longfei; Zhang, Yanbin; Jia, Lixin; Yang, Ningning
Abstract : This paper presents a modified modular multilevel converter (MMC) topology and a simple voltage balancing scheme that consists of intra‐ and inter‐arm voltage balancing methods. Each arm of the modified MMC comprises several half‐bridge submodules (SMs), one modified full‐bridge SM, and some clamping diodes. By adding a clamping diode to each of the two adjacent SMs, the capacitor voltage of one SM will be clamped by the two neighboring SMs when the clamping diode is in operation. Based on the diode‐clamped circuit, a simplify intra‐arm voltage balancing method, which needs only two voltage sensors, is proposed, and it takes up very little time for calculation and control. Moreover, an inter‐arm voltage balancing method based on bidirectional DC–DC converter control is studied, which can regulate the voltage balancing of two arms in one phase by controlling the power transmission amount and direction between two modified full‐bridge SMs. Compared with previous works, the present design prevents the MMC common mode current component to be injected into the grid and avoids interferences with system input or output voltage and current. Finally, a modified MMC system is built by using the PSCAD/EMTDC software, and the simulation results verify the effectiveness of the proposed topology and voltage balancing methods. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.